Hubungan Dukungan Keluarga Dengan Tingkat Stres Pada Lansia di Lingkungan V Kelurahan Bailang Kecamatan Bunaken - Sukma Manahapu; I Made Rantiasa; Bayu Dwisetyo (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2023)
Family support is a form that should be given to the family that is included in the implementation of stress on the elderly because through the family health problems can arise and can be overcome.This study aims to find out if there is a relationship between family support and the stress level of the elderly in the poor environment v poor environment The objective of the research employed in this study is to describe the nature or qualities of a symptom, event, or occurrence that is currently taking place. The methodology used is quantitative research with a descriptive analytical research design. Cross tabulation statistical tests showed that there was no relationship between family support and stress levels in the elderly in the Bailang district of Bunaken. The study used the spearman rank test, with the result of the correlation coefficient analysis obtained a value (P) = 0.905 ≥ α. Based on the results of the research, analysis of data, and discussion, it can be concluded that: Family support for the elderly in the Environment V Kelurahan Bailang District Bunaken majority is good. Stress level in the Elderly In the Environments V kelurahan bailang district Bunaken is severe majority. There is no significant relationship of family support with the stress level in older persons in the neighborhoods V Kelorahan Bailang Districts Bunaken (p≥0,05) with a weak non-significance of 0.905